Issues in healthcare reforms / Mohammed Fauzi Abdul Rani. - Abdul Rani, Mohammed Fauzi (Universiti Teknologi MARA Cawangan Selangor, 2018)
The recent 14th General Election signalled a fundamental change in the way this country had been governed since independent. For more than 6 decades, a single coalition government was in power, the victory of hope coalition parties or known as PH ushered a new era of change and enthusiasm with a genuine desire for good governance and transparency [1]. This is a calling that had permeated all government ministries [2] including the Ministry of Health (MOH). The appointment of an energetic yet ideological new health minister, an Imperial College London trained toxicologist to head the ministry and reign in all issues regarding health heightened the clamour to reform and improve our healthcare system, to face challenges of a changed nation and people, and the future.